2018
DOI: 10.3389/fped.2018.00109
|View full text |Cite
|
Sign up to set email alerts
|

Impaired FGF10 Signaling and Epithelial Development in Experimental Lung Hypoplasia With Esophageal Atresia

Abstract: Patients with esophageal atresia (EA) and tracheoesophageal fistula (TEF) often experience persistent respiratory tract disease. In experimental models, doxorubicin-induced developmental lung abnormalities may result from downregulation of branching morphogenesis factor fibroblast growth factor (Fgf10). This study investigated the temporospatial expression of Fgf10 pathway components and lung epithelial factors in an doxorubicin-induced EA-TEF model by quantitative polymerase chain reaction, immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“… 320 Studies using rat doxorubicin-induced EA-TEF (esophageal atresia-tracheoesophageal fistula) model have found that disturbed FGF10/CTSH signaling is associated with impaired airway branching and consequent impairment of epithelial cells in the lung. 321 BPD model established by exposing newborn mice to sublethal hyperoxia shows decreased expressions of FGFR3 and FGFR4 . 322 Klotho knockout mice show COPD and airway inflammation with elevated FGFR4 in the lung, whereas airway inflammation was attenuated in mice with overexpression of klotho.…”
Section: Fgf Signaling In Lung Development and Diseasesmentioning
confidence: 99%
“… 320 Studies using rat doxorubicin-induced EA-TEF (esophageal atresia-tracheoesophageal fistula) model have found that disturbed FGF10/CTSH signaling is associated with impaired airway branching and consequent impairment of epithelial cells in the lung. 321 BPD model established by exposing newborn mice to sublethal hyperoxia shows decreased expressions of FGFR3 and FGFR4 . 322 Klotho knockout mice show COPD and airway inflammation with elevated FGFR4 in the lung, whereas airway inflammation was attenuated in mice with overexpression of klotho.…”
Section: Fgf Signaling In Lung Development and Diseasesmentioning
confidence: 99%
“…Similarly, expression of a Fgfr2b ligand trap in pig lung epithelium inhibited normal branching (Q. Chen, Fang, et al, 2018). In an experimental model of doxorubicin‐induced lung hypoplasia, decreased expression of Fgf10 and its downstream effectors, Bmp4 and Cathepsin H ( Ctsh ) were associated with impaired airway branching and epithelial cell development (J. Wang, Liu, et al, 2018). Timed inhibition of FGF10 through the induced expression of a soluble FGFR2b ligand trap showed that FGF10 regulates lobular septation of the right lung at mouse embryonic day 9 (E9) and regulates branching morphogenesis after E11 (Taghizadeh et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Additionally, in congenital cystic adenomatoid malformation (CCAM), FGF10, FGF7 , and FGFR2 gene levels are unchanged in the lung mesenchyme ( Cass et al., 1998 ; Jancelewicz et al., 2008 ), whereas epithelial FGF9 expression is increased 4-fold in the CCAM samples compared to controls ( Jancelewicz et al., 2008 ). Furthermore, there is no evidence of altered FGF10 expression or signaling in human congenital small lung or lung hypoplasia, although its expression is different in mouse and rat experimental models of hypoplasia ( Teramoto et al., 2003 ; Wang et al., 2018 ). However, a decrease in FGF18 expression has been described in hypoplastic lungs from patients with congenital diaphragmatic hernia ( Boucherat et al., 2007 ).…”
Section: Fgf10 In Pediatric Human Lung Diseasesmentioning
confidence: 99%